Frustration and Aggression as the Basic Factors of Workersâ Strike: A Case Study on Railway Workersâ Strike in Semarang, Central Java, in the Colonial Era - Yuliati, Dewi (TAWARIKH, 2010)
ABSTRACT: This research aims to analyze the basic factors of the railway workersâ strike in Semarang, Central Java, in the Dutch colonial era. Historical method, that is finding and examining the historical records, was used to get authentic and credible facts. The historical analysis was supported by other relevant social sciences concepts, especially psychology, sociology, and politics to reach the objective construction of the history of railway workersâ strike in Semarang. The result of this research can be summarized as follows. Semarang, a city which has been industrialized since the middle of the 19th century, is a nutritious area for the growth and the development of industrial community which consists of employer and worker classes. In this industrial community, capitalism lacking of appreciation to the workersâ force led the workers to frustration. Frustration could make every human being or even animal aggressive. This research shows that âfrustration and aggressionâ are the basic factors of the workersâ movement, among others in the form of strike. KEY WORDS: workersâ strike and movement, frustration and aggression, Semarang city, and colonial era in Indonesia.About the Author: Dr. Dewi Yuliati is a Lecturer at the Department of History, Faculty of Cultural Sciences UNDIP (Diponegoro University) in Semarang, Central Java, Indonesia. She can be reached at: dewi_yulliati@yahoo.co.idHow to cite this article? Yuliati, Dewi. (2010). âFrustration and Aggression as the Basic Factors of Workersâ Strike: A Case Study on Railway Workersâ Strike in Semarang, Central Java, in the Colonial Eraâ in TAWARIKH: International Journal for Historical Studies, Vol.1(2) April, pp.179-200. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (February 7, 2010); Revised (March 11, 2010); and Published (April 28, 2010).